LEGAL PROTECTION OF REGISTERED MARKS IN INDONESIA BASED ON LAW NO. 20 OF 2016 ABOUT BRANDS AND GEOGRAPHICAL INDICATIONS - Eddy Syahputra; Hamdan Azhar Siregar (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
Legal protection of registered trademark rights in Indonesia based on Law No. 20 of 2016 concerning marks and geographical indications. research objectives, To find out the Development of Intellectual Property Rights (IPR) in Indonesia, especially in the field of Brands. To know and analyze the legal protection of trademark rights in Indonesia in the implementation of the TRIPs agreement based on Law No. 20 of 2016. To find out the government's efforts in preventing brand counterfeiting in the implementation of TRIPs approval, the Research Method is to use qualitative research methods that are normative. Research Results If the world of trade is getting more advanced, transparency tools are getting better, and also the number of promotional tools, it makes the marketing area expand, so that this situation adds to how important the meaning of a brand is to distinguish the origin of quality product results. This is to prevent imitation or use of the brand without rights, the law is basically a rule deliberately created by the community in order to achieve an orderly, safe, and peaceful life. Conclusion Brands that have not obtained legal protection regarding the rights to their marks, to obtain legal protection first apply for registration in Indonesia, if it turns out that the registered mark has been registered by another party, then the legal remedy that must be taken is to file a lawsuit for cancellation of the registered mark.